Modern Philosophy of Science and Its Implications for Strengthening the Professionalism of Guidance and Counseling Teachers: A Literature Review - Salwa Desti Zulfiakansa; Akhmad Fajar Prasetya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the contribution of modern philosophy of science and its impact on improving the professionalism of Guidance and Counseling (BK) teachers using a literature review method. The study focuses on ontology, epistemology, and axiology as the basis for developing BK knowledge and professional practice. The methodology applied is qualitative, with data collection conducted through a review of academic journals and relevant books, which are then processed using thematic analysis. The findings of this study indicate that the philosophy of science provides a solid conceptual framework for BK as an organized, reflective, and ethical discipline. This philosophical understanding has an impact on improving the professionalism of guidance counselors, especially in honing scientific thinking, making ethical decisions, demonstrating a reflective attitude, and maintaining moral integrity in the provision of services. Thus, the application of modern philosophy of science is strategically important in improving the professionalism of guidance counselors who are responsive, humane, and in line with changes in education today.